2010
DOI: 10.1016/j.physc.2009.10.142
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid density of Ba(Fe1-xMx)2<

Abstract: The temperature dependence of the ab-plane optical reflectivity of Ba(Fe0.92Co0.08)2As2 and Ba(Fe0.95Ni0.05)2As2 single crystals is measured in a wide spectral range. Upon entering the superconducting regime, the reflectivity in both compounds increases considerably at low frequency, leading to a clear gap in the optical conductivity below 100 cm −1 . From the analysis of the complex conductivity spectra we obtain the penetration depth λ(T ) = (3500 ± 350)Å for Ba(Fe0.92Co0.08)2As2 and (3000 ± 300)Å for Ba(Fe0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In our previous study of this material, we noted that it fell on the general scaling line originally observed for the high-temperature superconductors [36,37], recently demonstrated for some of the iron-based materials [70], ρ s0 /8 4.4 σ dc T c , where σ dc is measured just above T c . A natural consequence of the BCS theory in the dirty limit is the emergence of a similar scaling line [37,71] ρ s0 /8…”
Section: Parameter Scalingsupporting
confidence: 67%
“…In our previous study of this material, we noted that it fell on the general scaling line originally observed for the high-temperature superconductors [36,37], recently demonstrated for some of the iron-based materials [70], ρ s0 /8 4.4 σ dc T c , where σ dc is measured just above T c . A natural consequence of the BCS theory in the dirty limit is the emergence of a similar scaling line [37,71] ρ s0 /8…”
Section: Parameter Scalingsupporting
confidence: 67%
“…(b) Reflectivity measurements performed by different groups yield a very similar behavior at low temperatures. The solid line was obtained by Wu et al[29,30] on Ba(Fe 0.92 Co 0.08 ) 2 As 2 at T = 9 K. Kim et al[31] investigated Ba(Fe 0.935 Co 0.065 ) 2 As 2 at T = 5 K (blue dashed curve). The green dotted curve corresponds to a measurement of van Heumen et al[32] on Ba(Fe 0.93 Co 0.07 ) 2 As 2 at T = 10 K. Nakajima et al[21] investigated Ba(Fe 0.94 Co 0.06 ) 2 As 2 (dot-dashed red line) and Ba(Fe 0.92 -Co 0.08 ) 2 As 2 (dot-dot-dashed orange line) single crystals with T c = 25 and 20 K, respectively.…”
mentioning
confidence: 55%
“…The behavior of Ba(Fe 0.95 Ni 0.05 ) 2 As 2 is very similar to the optimally doped Co samples [29,30]. The reflectivity turns up around 60 cm −1 and approaches unity in way that the optical conductivity becomes gapped with 2∆ (1) 0 /hc = 35 cm −1 .…”
Section: Single Crystalsmentioning
confidence: 73%
“…(1), to include the SC critical temperature T c , Only data points obtained from optical spectroscopies (IR and MW SI) are included in the plot. The data points are from: cuprates ab-plane [2,11,12], cuprates c-axis [2], pnictides [13,14], elements [2], TiN [15], Ba1−xKxBiO3 [16], MgB2 [17,18], organic SC [19][20][21], fullerenes [22], heavy fermion CeCoIn5 [23], negative-U induced SC TlxPb1−xTe [24] and Y2C2I2 [25].…”
Section: Resultsmentioning
confidence: 99%